Mitigation of Cyano-HABs in surface water through preventative measures, and advanced monitoring & treatment - Antoniou, Maria G. (My University, 2026)
Invited Presentation at the research group of Dr. Soryong (Ryan) Chae at the Department of Environmental Engineering, University of Cincinnati